Financial Resilience: Financial Behavior and Financial Literacy Influence Digital Asset Management - Liliek Nur Sulistiyowati; Ririh Anggraini Setyahety; Adinda Maratusholikhah; Eka Listiana (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This research on financial resilience is designed to analyze how financial behavior and financial literacy contribute to Digital Asset Management among Millennials and Generation Z residing in the Madiun Residency. Background Problems: The financial technology (fintech) sector has experienced rapid expansion in recent years, transforming conventional financial systems into more digitalized and accessible ecosystems. One notable development is the increasing adoption of digital assets, including cryptocurrencies and security tokens, which has introduced new mechanisms in investment and financial management. Millennials and Generation Z, known for their familiarity with technology and digital platforms, represent a dominant segment in digital asset ownership. Novelty: This study contributes to the existing literature by integrating financial behavior and financial literacy as determinants of digital asset management. Research Methods: The research employed a quantitative approach involving 400 respondents from the Millennial and Generation Z populations in the Madiun area. Data were analyzed using descriptive statistical techniques and multiple linear regression analysis to evaluate both individual and simultaneous effects of the independent variables on digital asset management. Findings/Results: The empirical findings reveal that financial behavior and financial literacy each exert a statistically significant influence on digital asset management. Moreover, when examined together, both variables demonstrate a significant simultaneous effect, indicating their complementary role in shaping structured digital investment management. Conclusion: The study concludes that strengthening financial behavior and enhancing financial literacy are essential strategies for improving digital asset management among Millennials and Generation Z in the Madiun Residency.